A multiple test arbors-based calibration method for a hybrid machine tool. (April 2023) - Li, Mengyu; Wang, Liping; Yu, Guang; Li, Weitao; Kong, Xiangyu
Highlights: Multiple test arbors are used to calibrate the hybrid machine tool without orientation measurement. Two measurement schemes are proposed according to whether the ball diameters of the test arbors are the same. The measurement implements and measurement procedure are simple and the calibration efficiency is high. High calibration accuracy can be effectively ensured throughout the working space, even after tool replacement. The proposed method is verified by simulations and experiments. Abstract: Kinematic calibration is a necessary way to guarantee the accuracy of hybrid machine tools. The traditional calibration methods have high requirements for the measuring instruments and the measurement environment, and the measurement is extremely complex. The contradiction between measurement complexity and identification accuracy is an important problem in calibration. In this paper, a multiple test arbors-based calibration method for a hybrid machine tool is presented. The tool center point (TCP) position errors of multiple test arbors are measured sequentially by virtual TCP position constraints. The error parameters can be accurately identified based on these position errors without orientation measurement. The corresponding measurement scheme is described in detail according to whether the ball diameters of the test arbors are the same. The influence of the length and number of test arbors on the calibration results is investigated, and the basic principle for the selection of test arbors is given. Finally, the proposed method is validated by simulations and experiments. The proposed method can achieve overall high-accuracy calibration with simple measurement devices and convenient measurement steps, which provides a basis for automated calibration. Graphical abstract: Image, graphical abstract